Administration of Rescue Surfactant by Laryngeal Mask Airway: Lessons from a Pilot Trial - Attridge, Joshua T.; Stewart, Corrine; Stukenborg, George J.; Kattwinkel, John (American Journal of Perinatology, 2013)
Objectives To determine if surfactant can be effectively administered to larger preterm babies by laryngeal mask airway (LMA), reducing the need for supplemental oxygen.Study Design Enrollment criteria: birth weight > 1200 g, < 72 hours old, treated with nasal continuous positive airway pressure (nCPAP) for respiratory distress syndrome, with fraction of inspired oxygen (Fio2) requirement between 0.30 and 0.60. Subjects were randomized either to receive 3 mL/kg calfactant by LMA (experimental) followed by LMA removal back to CPAP, or continued on nCPAP (control). After intervention, both groups remained on nCPAP with Fio2 adjusted to maintain O2 saturations at 88 to 95%.Results A total of 26 patients (13 per group) were randomized, and 24 completed the study (11 experimental, 13 control). Groups were similar with respect to gender, mode of delivery, estimated gestational age, birth weight, and oxygen and pressure requirements at enrollment. Infants enrolled in the treatment group had an abrupt and sustained decrease in oxygen requirement after LMA surfactant therapy.Conclusion This pilot study demonstrates that surfactant can be delivered by LMA, which leads to a significant decrease in supplemental oxygen requirement. Larger controlled trials in low-resource settings may show this technique to be valuable in clinical situations where direct laryngoscopy and intubation are difficult or where resources for mechanical ventilation are limited.
Keywords: laryngeal mask airway; surfactant therapy; CPAP; respiratory distress syndrome